A Novel Centrifugal Filtration Device - Chia-Cheng Lin; Jung-Ming Wu (Separations, 2022)
In the proposed centrifugal filtration device, a filter is mounted in the center of the centrifugal chamber. The particles move towards the centrifuge wall away from the filter under centrifugal force, so a filtration cake is unlikely to accumulate here. The working fluid is injected continuously, so the feed pressure is higher than the discharge pressure, which compels the light-phase fluid to leave through the filter as filtrate. The filtrate flux rate and the movement of particles in the centrifugal chamber of the proposed filtration device were investigated using different powder particle sizes, concentrations of working fluid, centrifugal chamber rotation speeds, and filters. With a higher centrifugal chamber rotation speed, the centrifugal force acting on the particles in the centrifugal chamber was stronger, and the particles were less likely to adhere to the central filter; hence, a larger amount of filtrate was produced.